Towards smart manufacturing process selection in Cyber-Physical Systems. (August 2018) - Ndip-Agbor, Ebot; Cao, Jian; Ehmann, Kornel
Abstract: Cyber-Physical Systems (CPS) are becoming increasingly important in manufacturing due to the digitization of the industry driven by advances in technology and connectivity. However, the variation of process selection criteria, both geometric and non-geometric, across the main groups of manufacturing processes, i.e., additive, subtractive, and deformation, makes it difficult to implement smart manufacturing process sequence selection which is an essential step toward achieving an autonomous CPS. This paper presents a conceptual solution to process selection called Constraint Satisfaction Problem for Manufacturing (CSP4M) which leverages current engineering design methods and architectures.